Geografías del conocimiento: Perspectivas de mujeres científicas en la construcción de una Iberoamérica sostenible - HERNÁNDEZ DE GANTE, ALICIA; BARRIOS DEL ANGEL, ANA XOCHITL; González-Hernández, Andrés; Barragan Flores, Anette Michaelle; Mendieta Ramírez, Angélica; Briseño, Arturo; Larrondo, Astrid; Gatica-Gómez, Avecita; Díaz Mariño, Blanca Leticia; Bucio Gutierrez, Daniel; Arvizu, Eduardo; Hernández-Rejón, Elda Margarita; et al. (High Rate Consulting, 2026)
Geographies of Knowledge: Perspectives of Women Scientists in the Construction of a Sustainable Ibero-America brings together research that highlights the active role of women in transforming scientific practices and in linking knowledge to the social, territorial, and environmental challenges faced by our countries. The contributions span diverse fields—from the humanities and social sciences to education, organizational studies, and Earth sciences—and demonstrate how research conducted by women influences communities, institutions, and decision-making processes. Throughout its chapters, the book addresses themes such as women’s leadership, sustainability, food sovereignty, territorial development, entrepreneurship, and social justice, underscoring the importance of incorporating experience and a gender perspective into knowledge production. This volume goes beyond compiling research findings; it also reveals that knowledge is constructed within specific historical and territorial contexts. The trajectories, experiences, and positions of the authors broaden the understanding of contemporary issues and provide key insights for envisioning more equitable development alternatives. The “geographies” presented here refer not only to physical spaces but also to the social, cultural, and ethical dimensions of scientific practice. Taken as a whole, the book offers a plural vision of women’s contributions to Ibero-American science and emphasizes their central role in shaping more sustainable futures.